2011
DOI: 10.1074/jbc.m110.157362
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Role of Microsomal Prostaglandin E Synthase-1 in a Model of Neuroinflammation

Abstract: A major immunological response during neuroinflammation is the activation of microglia, which subsequently release proinflammatory mediators such as prostaglandin E 2 (PGE 2 ). Besides its proinflammatory properties, cyclooxygenase-2 (COX-2)-derived PGE 2 has been shown to exhibit anti-inflammatory effects on innate immune responses. Here, we investigated the role of microsomal PGE 2 synthase-1 (mPGES-1), which is functionally coupled to COX-2, in immune responses using a model of lipopolysaccharide (LPS)-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 52 publications
0
40
0
Order By: Relevance
“…Lipopolysaccharide-evoked synthesis of pro-inflammatory cytokines such as interleukin-1β (IL-1β) and tumor necrosis factor α (TNFα) has been shown to trigger induction of mPGES-1 in neurons and microglia in spinal neuroinflammation (39). It has also been shown that cytokines including IL-1β and TNFα were up-regulated in the degenerating spinal cords in G93A mice (40).…”
Section: Discussionmentioning
confidence: 88%
“…Lipopolysaccharide-evoked synthesis of pro-inflammatory cytokines such as interleukin-1β (IL-1β) and tumor necrosis factor α (TNFα) has been shown to trigger induction of mPGES-1 in neurons and microglia in spinal neuroinflammation (39). It has also been shown that cytokines including IL-1β and TNFα were up-regulated in the degenerating spinal cords in G93A mice (40).…”
Section: Discussionmentioning
confidence: 88%
“…The following review will serve to highlight and discuss the underrepresented regulatory role of the PCPP axis in each of these processes within the context of rheumatoid (''inflammatory'') arthritis. It should be emphasized, however, that the concepts presented herein are not unique to RA and are generally relevant to other inflammatory disorders (e.g., neuroinflammatory disorders [36], hepatic inflammation [37], airway inflammation [38][39][40]). …”
Section: Introductionmentioning
confidence: 99%
“…The residues were reconstituted with 50 ml of acetonitrile:water:formic acid (20:80:0.0025, v/v, pH 4) and injected into the LC-MS/MS. PGs were separated with a Synergi 150 3 2.0 mm Hydro-RP column (Phenomenex, Aschaffenburg, Germany) and determined with a triple quadrupole MS (5500 Q-TRAP; Sciex, Darmstadt, Germany) (27).…”
Section: Pg Determinationmentioning
confidence: 99%